Validation of pairs of antagonist teeth for the evaluation of shortened dental arch in epidemiological studies - Fernanda Lamounier CAMPOS; Gabriela Aparecida Caldeira RHODES; Walison Arthuso VASCONCELLOS; Rafael Aiello BOMFIM; Aline Araujo SAMPAIO; Loliza Luiz Figueiredo Houri CHALUB; Raquel Conceição FERREIRA (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to evaluate the accuracy of pairs of antagonist teeth (epidemiological criterion) for defining pairs of teeth in occlusal contact (clinical criterion) and to estimate the agreement between the prevalence of "shortened dental arch" (SDA) and "functional dentition" (FD) when occlusal units (OUs) or posterior occluding pairs (POPs) are defined by the epidemiological or clinical criterion. Data were collected in an epidemiological oral health survey conducted in a municipality in Minas Gerais, Brazil. OUs and POPs were defined by the epidemiological criterion (dental crown status) or clinical criterion "gold standard" (carbon paper record of occlusal contacts during habitual maximum intercuspation). SDA corresponded to the presence of an intact anterior region and three to five OUs. FD was based on the concomitant presence of ≥ 1 tooth in each arch, 10 teeth in each arch, 12 anterior teeth, ≥ 3 premolar POPs, and ≥ 1 molar POP bilaterally. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of the epidemiological criterion were calculated. The study included 197 adults. Sensitivity, specificity, PPV, and NPV were 88.5, 87.9, 92.5, and 81.9%, respectively, and accuracy was 88.3%. The epidemiological criterion proved to be valid and could be used in epidemiological studies to calculate the prevalence of reduced dental configurations that consider POPs. The assessment of oral functionality is an aspect that should be included in the diagnosis of the clinical condition of patients, contributing to a more effective individual and collective oral health care plan.